New Zealand's Fiscal Policy Framework: Experience and Evolution - John Janssen (New Zealand Government, The Treasury, 2001)
Fiscal policy in New Zealand has seen a consolidation of the Government's position and continuing refinements to the institutional framework and Budget processes. The key institutional change has been the introduction of the Fiscal Responsibility Act 1994. The paper sets out the background to the fiscal policy framework, including fiscal history and various institutional changes in the public sector. This paper is a companion paper to Treasury Working Paper 01/24 by Angela Barnes and Steve Leith. The key elements of the fiscal policy framework are explained and compared to various "fiscal rules" used internationally. The New Zealand framework differs from that used elsewhere, especially in its use of legislated "principles of responsible fiscal management" as opposed to mandatory targets. However, the Fiscal Responsibility Act 1994 does require Governments to set short-term fiscal intentions and long-term fiscal objectives for a range of fiscal aggregates. The paper discusses the experience with the framework including a comparison of fiscal outcomes with fiscal objectives. The New Zealand experience has seen the evolution of specific operational targets (the fiscal provisions) to help improve the consistency of short-term intentions with longer-term fiscal objectives. The paper concludes with a set of challenges facing the framework, both short- and long-term.
Keywords: E62; H61; 330; Fiscal policy; Fiscal Responsibility Act